Maintenance of National Heritage Anglican Churches in Malaysia - Wee Fhong Ow; Shirley Jin Lin Chua; Azlan Shah Ali (Advances in Civil Engineering)
This paper addresses the maintenance of National Heritage Anglican churches in Malaysia. A field survey is presented, describing the current defects of selected Anglican churches in Malaysia and proposing maintenance practices against the identified defects. The neglect in maintaining Anglican churches is alarming. The survey revealed that, aside from routine housekeeping, the majority of the churches surveyed had little to no regular maintenance. As the studied Anglican churches are Malaysian’s National Heritage, the study adopted AHP and ANP to determine the relative importance of building discipline and space type inside a church, ensuring that the maintenance shall not neglect the values of these entities. Collectively, the in-situ survey results, the maintenance practices recommended by past literature, and the relative importance of building discipline and space type were used to propose a maintenance plan. Instead of generalising areas inside a church, different areas within a church are weighted differently in terms of importance levels, especially due to the fact that churches have a substantially different occupancy rate than conventional buildings. With the proposed hierarchy, priority might be given to the most vital areas first. In addition, church assets differ from those of other types of buildings, and their features should not be addressed in the same way. The research gives an improved asset hierarchy for churches based on the findings of multicriteria decision-making analysis. With this hierarchy in place, building custodians or maintenance personnel may find it easier to prioritise maintenance activities at churches, especially when financial is often limited.